Regional Government PR Synergy in Countering Hoaxes and Enhancing Digital Literacy in Bengkulu: A Phenomenological Study - Tri Wahyuniarti; Alib Prihantoro Putro; Dyah Noor Intan (Universitas Ahmad Dahlan, 2026)
The spread of hoaxes on digital platforms has become a significant challenge in Indonesia, particularly in Bengkulu Province. This study examines the role of local government public relations, media, and influencers in combating hoaxes and improving digital literacy among the public. Employing a qualitative approach with a phenomenological design, this research explores the collaborative strategies and lived experiences of key stakeholders. Data were collected through in-depth interviews, focus group discussions, and document analysis. The findings highlight the importance of collaboration between the government, media, and influencers in creating effective digital literacy campaigns. The study reveals a critical communication gap, where government PR has not fully optimized the role of influencers as strategic